Cultivating the capacity for active balancing during adolescence: pathways to a coherent self - Juneja, Abhishek; Hansen, David M.; Lemon, Michael P. (Frontiers in Developmental Psychology, 2024)
In this paper we propose that one of the core developmental aims of adolescence is to cultivate a capacity for active balancing as the primary process for creating a coherent, agentic self capable of contributing to the functioning and purposes of the communities which adolescents inhabit, including society as a broader community. While there many valuable initiatives and programs to promote positive development, learning, and well-being, these efforts typically take a siloed approach focusing on one dimension of development (e.g., social-emotional learning), leaving adolescents to create coherence from these disconnected approaches. As adolescence face an increasingly uncertain future (e.g., career instability), serious threats to human survival (e.g., environmental degradation), social divides (e.g., political and ideological polarization), etc., a siloed approach to adolescent development is not simply outmoded but it reinforces a fragmented self. Conceptual Model & Background. In this paper we argue that a siloed approach to adolescent development and learning may contribute to a fragmented sense of self and agency, which can be associated with increased vulnerability to mental health challenges. We first link the proposed developmental aim of adolescence to neuroscience findings that identify three brain changes during adolescence that lay the groundwork for cultivating active balancing and provide an ontogenetic neurological push for adolescents to learn and manage how to engage their worlds. Leveraging this ontogenetic push, we propose adolescents can cultivate their capacity for active balancing within the cultural communities of practice they inhabit. These communities provide a ready and powerful fusion of action, affect, and thought into coherent and relevant understandings of the why, how, and utility of practices in a community, or what we label orientations. Active balancing is the process of actively seeking to establish or reestablish one's intended balance among these orientations. Conclusions & Implications. Building the capacity for active balancing, we suggest, engenders greater resilience and adaptability to a range of situations, a tolerance for and ability to resolve tensions, and an ability to transcend vast differences, including cultural and ideological. Implications for both the adolescent and society are discussed.